PID controller using Zieglar-Nichols an chien tuning process for liquid level control of coupled tanks system / Mohd Hanashan Daud - Daud, Mohd Hanashan (2007)
Nowadays, industries such as petroleum, petrochemical industries and drinking water industries like Petronas and Coca Cola are the essential industries where liquid level and liquid flow need to he controlled. This paper proposes the PID (Proportional Integral Derivative) controller on the coupled tanks system that allows controlling the liquid level in the second tank or tank 2. The flows between tanks also need to be considered in the presence of nonlinearity and inexact model description of the plant. The proposed of PID controller in this paper is to get the best settling time for steady state error elimination to reach its set point or desired liquid level by using Zieglar-Nichols and Chien tuning process technique. The appropriate control signal is produced by simulation studies based on the developed model using MATLAB and S1MULINK.